Phenolics, flavonoids, antioxidant activity and cyanogenic glycosides of organic and mineral-base fertilized cassava tubers - Omar, Nur Faezah; Hassan, Siti Aishah; Yusuf, Umi Kalsom; Abdullah, Nur Ashikin Psyquay; Megat Wahab, Puteri Edaroyati; Sinniah, Uma Rani (MDPI, 2012)
A field study was conducted to determine the effect of organic and mineral-based fertilizers on phytochemical contents in the tubers of two cassava varieties. Treatments were arranged in a split plot design with three replicates. The main plot was fertilizer source (vermicompost, empty fruit bunch compost and inorganic fertilizer) and sub-plot was cassava variety (Medan and Sri Pontian). The amount of fertilizer applied was based on 180 kg K2O ha−1. The tubers were harvested and analyzed for total flavonoids, total phenolics, antioxidant activity and cyanogenic glucoside content. Total phenolic and flavonoid compounds were determined using the Folin-Ciocalteu assay and aluminium chloride colorimetric method, respectively. Different sources of fertilizer, varieties and their interactions were found to have a significant effect on phytochemical content. The phenolic and flavonoid content were significantly higher (p < 0.01) in the vermicompost treatment compared to mineral fertilizer and EFB compost. The total flavonoids and phenolics content of vermicompost treated plants were 39% and 38% higher, respectively, than those chemically fertilized. The antioxidant activity determined using the DPPH and FRAP assays were high with application of organic fertilizer. Cyanogenic glycoside levels were decreased with the application of organic fertilizer. Among the two types of compost, vermicompost resulted in higher nutritional value of cassava tubers. Medan variety with application of vermicompost showed the most promising nutritional quality. Since the nutritional quality of cassava can be improved by organic fertilization, organic fertilizer should be used in place of chemical fertilizer for environmentally sustainable production of better quality cassava.